Evaluation and comparison of pain questionnaires for clinical screening of osteoarthritis in cats. (21st December 2019) - Stadig, Sarah; Lascelles, B Duncan X; Nyman, Gorel; Bergh, Anna
Abstract : Background: Feline osteoarthritis (OA) is a common cause of long‐standing pain and physical dysfunction. Performing a physical examination of a cat is often challenging. There is a need for disease‐specific questionnaires or the so‐called clinical metrology instruments (CMIs) to facilitate diagnosis and evaluation of treatment of feline OA. The CMI provides the owners an assessment of the cat's behavioural and lifestyle changes in the home environment. The purpose of the study was to evaluate readability, internal consistency, reliability and discriminatory ability of four CMIs. Methods: This is a prospective, cross‐sectional study with 142 client‐owned cats. Feline OA was diagnosed based on medical history, orthopaedic examination and radiography. Results: The results indicate that all four instruments have sound readability, internal consistency, are reliable over time and have good discriminatory ability. Preliminary cut‐off values with optimal sensitivity and specificity were suggested for each instrument. The osteoarthritic cats showed significant changes in behavioural response to pain during orthopaedic examination, compared with sound cats. Conclusion: The results indicate that all four questionnaires make an important contribution in a clinical setting, and that the cat's behavioural response to pain during physical examination should be a parameter to take into account as a possible indication of chronic pain.